Constructing place : mind and matter - Menin, Sarah (Routledge, 2003)
"Constructing Place forges new collaborative ideas in an interdisciplinary way including essays on architecture, planning, landscape and philosophy (particularly applied aesthetics). Written for and by those in both practice and academia across this range of fields, it is also useful for those interested in psychology and creativity, and those who are keen on issues about the value of engagement with the environment."--Jacket